Persebaran Demam Berdarah Dengue Berdasarkan Faktor Kepadatan Penduduk, Curah Hujan, dan Angka Bebas Jentik (ABJ) di Kota Madiun - Aimmatus Shofifah; Anggara Widyartanto; Lilis Sulistyorini (Media Gizi Kesmas, 2023)
Background: Dengue hemorrhagic fever (DHF) is a disease caused by the dengue virus, the virus can spread and enter the human body carried by mosquitoes of the Aedes Aegypti and Aedes Albopictus types. Environmental influences can increase mosquito breeding such as temperature, rainfall, and humidity. Objectives: Dengue hemorrhagic fever (DHF) is a disease caused by the dengue virus, the virus can spread and enter the human body carried by mosquitoes of the Aedes Aegypti and Aedes Albopictus types. Environmental influences can increase mosquito breeding such as temperature, rainfall, and humidity. Objective: To find out the distribution of dengue cases in urban villages in Madiun City by utilizing spatial analysis. Methods: Quantitative analytic with secondary data analysis approach, the research design used was cross-sectional. This study uses a geographic spatial number approach for the analysis of risk factors for DHF related to DHF cases in Madiun City in 2020. Results: On average, the urban village had a number of cases from 1-7, namely as many as 20 villages, the average population density was in the range of 1775-5633 with 17 villages, the average village that was 16 villages had a 95%-97% free rate value, all villages had rainfall in the 100-300 mm time range, 21 villages had a DHF risk level score of 1- 2 and 6 villages had a score of 2-3. Conclusions: The average urban village in Madiun City has a population density in the low category. There are 7 sub-districts in Madiun City with ABJ scores below 95%. All sub-districts have moderate rainfall, namely 100-300 mm. A high level of dengue risk in an area does not necessarily indicate that dengue cases in that area are high. Prevention of dengue fever can be done to reduce the increase in cases.